2022
DOI: 10.1021/acssuschemeng.1c08434
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Crystals Confining Ultrathin MoS2 Nanosheets: A High-Concentration and Stable Aqueous Dispersion

Abstract: To realize the application potential of molybdenum disulfide (MoS 2 ) in aqueous environments, scalable and efficient methods for the preparation of high-concentration and stable dispersions need to be developed. In this paper, ultrathin MoS 2 successfully was synthesized using an in situ-exfoliated bulk MoS 2 method in water using ionic liquid crystals (ILCs) as green exfoliating/dispersing agents. The ILCs containing hydrophobic cations and hydrophilic anions not only help to exfoliate bulk MoS 2 into ultrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This may be attributed to the fact that small CDs were easily filled into the friction gap. With the deformation and failure of CDs, the remaining CDs will immediately supplement the friction gap, play a self-repairing role, and form a self-lubricating carbon film at the contact surface, showing relatively stable lubrication. The average friction coefficient and wear scar width of CDs with different concentrations are shown in Figure b. Compared with pure sunflower oil, the addition of CDs significantly reduced the average friction coefficient and wear scar width.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the fact that small CDs were easily filled into the friction gap. With the deformation and failure of CDs, the remaining CDs will immediately supplement the friction gap, play a self-repairing role, and form a self-lubricating carbon film at the contact surface, showing relatively stable lubrication. The average friction coefficient and wear scar width of CDs with different concentrations are shown in Figure b. Compared with pure sunflower oil, the addition of CDs significantly reduced the average friction coefficient and wear scar width.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing environmental pollution and energy problems, it has become a trend that oil-based lubricants are gradually replaced by environment-friendly lubricants . Ionic liquids and polar organic solvents are considered ideal lubricant fluids because of their high viscosity index, high flash point, high boiling point, low volatility, and low freezing point. In addition to their use as solvents, ionic liquids can be used as neat anticorrosion and antiwear lubricants with good lubricating properties. The ionic liquids can form strong structural boundary layers with low dissipation even at high pressures through van der Waals, electrostatic, and H-bonding interactions, which can act as a shield and buffer. The solid–IL interface can be divided into three different regions: the boundary layer, the transition zone, and the bulk phase .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to common surfactants, ILCs are green molten salts containing long flexible alkyl chains (C > 12), consisting of anions and cations. Their own low volatility, wide range of liquids, and non-flammability confer them great potential for application. , Especially, imidazolium-based ILCs possess excellent thermal stability due to the unique imidazole ring structure . In addition, Yan et al found that the imidazole ring of ILC can form cation−π bonds with graphene-like materials with π-conjugated structures and successfully constructed the reversible solution-processable hydrogels of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Especially, imidazolium-based ILCs possess excellent thermal stability due to the unique imidazole ring structure. 22 In addition, Yan et al found that the imidazole ring of ILC can form cation−π bonds with graphene-like materials with π-conjugated structures and successfully constructed the reversible solution-processable hydrogels of g-C 3 N 4 . 23 Furthermore, ILC-assisted exfoliation of graphite fluoride was reported to achieve simultaneous exfoliation and non-covalent functionalization of fluorinated graphene (FG), in which ILCs were attached to the surface of FG, enabling stable dispersion of the exfoliated FG.…”
Section: Introductionmentioning
confidence: 99%